Utilizing the Gastrointestinal Microbiota to Modulate Cattle Health through the Microbiome-Gut-Organ Axes - Christina B. Welch; Valerie E. Ryman; T. Dean Pringle; Jeferson M. Lourenco (Microorganisms, 2022)
The microorganisms inhabiting the gastrointestinal tract (GIT) of ruminants have a mutualistic relationship with the host that influences the efficiency and health of the ruminants. The GIT microbiota interacts with the host immune system to influence not only the GIT, but other organs in the body as well. The objective of this review is to highlight the importance of the role the gastrointestinal microbiota plays in modulating the health of a host through communication with different organs in the body through the microbiome-gut-organ axes. Among other things, the GIT microbiota produces metabolites for the host and prevents the colonization of pathogens. In order to prevent dysbiosis of the GIT microbiota, gut microbial therapies can be utilized to re-introduce beneficial bacteria and regain homeostasis within the rumen environment and promote gastrointestinal health. Additionally, controlling GIT dysbiosis can aid the immune system in preventing disfunction in other organ systems in the body through the microbiome-gut-brain axis, the microbiome-gut-lung axis, the microbiome-gut-mammary axis, and the microbiome-gut-reproductive axis.